EFFECTIVENESS OF NON-PROJECTED VISUAL RESOURCES IN LEARNING SOCIAL STUDIES BETWEEN MALE AND FEMALE’ STUDENTS IN JUNIOR PUBLIC SCHOOLS IN NORTH-WEST GEOPOLITICAL ZONE OF NIGERIA - Zubairu, Suleiman Abubakar (Sokoto Educational Review, 2011)
This study examined the effectiveness of non-projected visual resources in learning social studies in junior public schools in North-West Geopolitical Zone of Nigeria. One thousand one hundred and twenty (1120) students covering six states were involved in the study. They were randomly sampled from each state of the geopolitical zone. The opinion and data gathered from the respondents are analyzed using t-test statistical instrument. The result shows that effective utilization of nonprojected visual resources enhance learning while gender has no influence at all. The factor that militates against effective use of non-projected visual resources by teachers is negligence as well as teachers inadequacies in utilizing the resources. Recommendations were also made accordingly.